2017
DOI: 10.1055/s-0037-1603940
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Comparison of Enfamil and Similac Liquid Human Milk Fortifier on Clinical Outcomes in Premature Infants

Abstract: Objective To compare growth and metabolic outcomes of premature infants receiving either Enfamil liquid human milk fortifier (ELHMF) or Similac liquid human milk fortifier (SLHMF). Study Design Infants born at ≤31 weeks' gestational age (GA) with birth weights <1,500 g and exclusively fed on human milk (mother's milk and/or donor milk) were prospectively assigned alternatively to one of the two liquid human milk fortifier (LHMF) groups. Baseline demographic, growth, enteral nutrition, and labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…We did not consider here partially or extensively hydrolyzed fortifiers, now used in the United States. Such fortifiers have been compared with each other with some differences, [34][35][36][37] but not compared to HMDF for the broad range of morbidities differentially affected by CM versus HM exposure.…”
Section: Limitationsmentioning
confidence: 99%
“…We did not consider here partially or extensively hydrolyzed fortifiers, now used in the United States. Such fortifiers have been compared with each other with some differences, [34][35][36][37] but not compared to HMDF for the broad range of morbidities differentially affected by CM versus HM exposure.…”
Section: Limitationsmentioning
confidence: 99%
“…Two studies compared the different compositions of fortifiers [42,51]. Porcelli et al compared Wyeth Nutritional International's new HMF (test) with Enfamil HMF (reference); the authors reported an improvement in weight gain (19.7 vs. 16.8 g/kg/d, p = 0.04); however, no effect was observed on length gain [51].…”
Section: Different Formulasmentioning
confidence: 99%
“…This study also found a positive effect on feeding outcomes; mean human milk intake was higher in test HMF compared to reference HMF. Similarly, Kumar et al compared Similac liquid HMF with Enfamil liquid HMF [42]; the authors reported better weight gain among infants fed with Similac liquid HMF.…”
Section: Different Formulasmentioning
confidence: 99%
“…The use of acidified HMF in VLBW infants is controversial, showing no advantages in growth in most studies (33)(34). These include a relatively large multicenter randomized trial that found higher rates of metabolic acidosis in infants using an acidified LHMF (35).…”
Section: Discussionmentioning
confidence: 99%